PENGARUH VARIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN SAMBAL INDOFOOD DI SUPERMARKET SARIKAT JAYA GRESIK - Farida, Nur (Fakultas Ekonomi Universitas Gresik, 2017)
Business competition occurs in both service and non-service industries. One of them is complementary food. The competition in this business is a very tight. This industry is a good topic to be discussed, because the complementary food is a necessity for the consumer. One of them is sambal which is a very special meal of Indonesian. One of the sambal product is Sambal Indofood which tries to do a strategy of product variation. This shows that competition among complementary foods is getting tighter.The purpose of this research is to determine the effect of product variation in Indofood sauce purchase decision. This research was conducted in Supermarket Sarikat Jaya Gresik. This research is explanatory type with quantitative approach. The sample is taken by accidental sampling technique with the total sample of 94 respondents. Data collection methods related to the research problem are conducted by using questionnaire method. The Data collection techniques are using questionnaires.The result of the research from 94 respondents show that the influence of product variation to purchase decision. From result of regression calculation by using SPSS program version 18.00 for windows, obtained tvalue counted equal to 6,416 with p value equal to 0.000. Using the significance limit ÃƒÆ’Ã†â€™Ãƒâ€¦Ã‚Â½ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â± = 0.05 obtained T table of 1.986. From these results then tcalculated > ttable which means Ho rejected and H1 accepted. It means variable product variation has a positive and significant influence in determining purchase decision of Sambal Indofood to consumers in Supermarket Sarikat Jaya Gresik.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3477677